Competency building for lay health workers is an intangible force driving basic public health services in Southwest China - Shengxiang Liang; Haoyue Deng; Shili Liu; Geng Wang; Li Li; Mei Wang; Jie Pu; Wei Xing; Xingneng Luo; John Ehiri; Yueying Xiang; Ying Li (BMC, 2019)
Abstract Background Providing universal basic public health services (BPHS) for residents is the main goal of the new health reform in China. Lay health workers (LHWs) in primary health care (PHC) sectors play key roles in BPHS delivery. The competency of LHWs is critical to quality BPHS. This study assessed LHWs' competency to deliver BPHS and related training in resource-limited Southwest China. Methods A mixed research method combining in-depth interviews with secondary data collection was used to collect data in this cross-sectional study. Fifty-four LHWs and 16 leaders in 16 PHC sectors were recruited for in-depth interviews. Secondary data on 198 LHWs were collected through standard forms. Results Both the interviews and secondary data suggested that all PHC sectors did not have sufficient LHWs and lacked qualified LHWs to deliver BPHS overall, particularly in relatively low economic rural areas in Guizhou province. Furthermore, PHC sectors had difficulties retaining existing LHWs due to low incomes and fewer opportunities for self-development. In-depth interviews discovered that, although numerous training opportunities have been provided for LHWs since 2009, the trainings did not achieve the expected outcome in LHW competency building, as LHWs actually did not have access to the trainings and the training design was unresponsive to the actual needs of LHWs. Both LHWs and leaders expressed an urgent need for effective training for LHWs based on systematic needs assessments and the use of qualified trainers and materials. Conclusions The shortage of qualified LHWs in PHC sectors became the bottleneck for BPHS delivery in Southwest China. Recent trainings for LHWs were less effective with regard to LHW competency building. A need-based professional training programme for LHWs by qualified trainers was expected by both LHWs and leaders in PHC sectors.